Sophrosyne and simulacra: probing the nature of a constructed self-image - Katić, Elvira K. (Signs - International Journal of Semiotics, 2009)
This essay resulted from an analysis of an artwork where the artist was motivated to construct a representation of herself. A social semiotic analysis of the self-image indicates interchangeability and tension among artistic elements with assumed, dialectically opposed meanings. Discussion with regards to the nature of the selfportrait touches on philosophically influenced interpretations that pose the image as a cyborg and the cyborg as a simulacrum. Upon reflection, the self-image can be interpreted as having the qualities of a simulacrum (a reproduction that is selfcontained and autonomous) more so than of an authentic expression of representation. This essay hopes to contribute to the continued critical examination of individual visual representations in order to help enrich the growing knowledge base from which we derive a fuller understanding of our surrounding culture and ourselves.